Polyelectrolyte-mediated increase of biofilm mass formation - Bucki, Robert (BMC Microbiol, 2015)
BACKGROUND: Biofilm formation is associated with various aspects of bacterial and fungal infection. This study was designed to assess the impact of diverse natural polyelectrolytes, such as DNA, F-actin, neurofilaments (NFs), vimentin and purified Pf1 bacteriophage on biofilm formation and swarming motility of select pathogens including Pseudomonas aeruginosa associated with lung infections in CF patients. RESULTS: The bacteriophage Pf1 (1 mg/ml) significantly increased biofilm mass produced by Pseudomonas aeruginosa P14, Escherichia coli RS218 and Bacillus subtilis ATCC6051. DNA, F-actin, NFs and Pf1 also increased biofilm mass of the fungal C. albicans 1409 strain. Addition of F-actin, DNA or Pf1 bacteriophage to 0.5% agar plates increased swarming motility of Pseudomonas aeruginosa Xen5. CONCLUSIONS: The presence of polyelectrolytes at infection sites is likely to promote biofilm growth and bacterial swarming.